2013
DOI: 10.1016/j.bbapap.2013.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The human secretome atlas initiative: Implications in health and disease conditions

Abstract: Proteomic analysis of human body fluids is highly challenging, therefore many researchers are redirecting efforts towards secretome profiling. The goal is to define potential biomarkers and therapeutic targets in the secretome that can be traced back in accessible human body fluids. However, currently there is a lack of secretome profiles of normal human primary cells making it difficult to assess the biological meaning of current findings. In this study we sought to establish secretome profiles of human prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 52 publications
(45 reference statements)
1
48
0
1
Order By: Relevance
“…This finding is similar to those of a recent study evaluating the ASL proteome of CF and non-CF HBE cultures, which demonstrated that the majority of differentially expressed proteins was elevated in CF (26). An unexpected finding was the inclusion of many intracellular proteins and membrane-associated proteins ( Figure 1D), with only 25.6% (z668 protein) of the total 2,608 proteins being classified as known secreted proteins (27) (Figure 1E, Table E2B). …”
Section: Defining the Smg Secretome From Cf And Non-cf Airways Using supporting
confidence: 78%
“…This finding is similar to those of a recent study evaluating the ASL proteome of CF and non-CF HBE cultures, which demonstrated that the majority of differentially expressed proteins was elevated in CF (26). An unexpected finding was the inclusion of many intracellular proteins and membrane-associated proteins ( Figure 1D), with only 25.6% (z668 protein) of the total 2,608 proteins being classified as known secreted proteins (27) (Figure 1E, Table E2B). …”
Section: Defining the Smg Secretome From Cf And Non-cf Airways Using supporting
confidence: 78%
“…Endocrine signaling between distant organ systems and tumor cells, as well as paracrine signaling between tumor and host cells in the local microenvironment, is mediated by an increasingly large roster of obesity-responsive hormones, growth factors, nutrient metabolites, chemokines and cytokines that promote tumor development and/or progression. To date, these factors (summarized below) have been studied primarily by low-throughput methods such as singleplexed or multiplexed immunoassays of serum, plasma or other biologic fluids, but high-throughput proteomic and metabolomic approaches to characterize the secretomes of organisms or cancer cells are being developed to more broadly identify the key factors (and their interactions) underlying disease states such as breast cancer [18]. …”
Section: Extrinsic Factors: the Secretome And The Soilmentioning
confidence: 99%
“…Astrocytes are the predominant source of brain Prdx6 (Asuni et al, 2014; Lafon-Cazal et al, 2003; Yang et al, 2005), and its expression has been documented in several cell compartments, including the cytoplasm, secretory organelles, lysosomes and mitochondria (Eismann et al, 2009; Immenschuh and Baumgart-Vogt, 2005; Peshenko et al, 1998; Wu et al, 2006). It is also present in CSF, plasma and urine (Brown et al, 2013). …”
Section: Introductionmentioning
confidence: 99%